Robotic automatization of handling and contacting the ends of windings for mounting electric drives - Kühl, Alexander; Lebender, Johannes; Franke, Jörg (Lecture Notes in Engineering and Computer Science, 2016)
The connecting process is still one of the most time-consuming processing steps in the production of electric drives. For this reason, the E|Drive-Center at the Institute for Factory Automation and Production Systems (FAPS) from Friedrich-Alexander University Erlangen-Nuremberg (FAU) is researching a solution centered on the flexible automation of this process. This paper examines the possibility of automating the contact of windings' ends in an asynchronous motor with a universal, ambidextrous robot using a contact base. Here, the related ends of the enameled copper wires are connected before plugging in the power supply. In doing so, the robot saves the ends directly after manufacturing the coils in a winding machine and transports them to the face side of the stator. The final connection with the motor periphery is implemented with termination clamps whereby a blade cuts through the wire insulation and produces an electrical connection, while the wiring for the motor concept is actualized by a wiring institution in the form of a plastic ring with printed conducting paths. This form of contacting the ends of windings while mounting an electric drive with a universal, ambidextrous robot has the potential to save time and improve process stability.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Automation; Connecting; robot; Contacting; Electrical drive production; Wiring